Caring for Archives of Incarceration: The Ethics of Carceral Collecting at University Archives - Robinson-Sweet, Anna (Archivaria)

(untitled) (Association of Canadian Archivists, 2024)
In recent years, university archives have initiated efforts to document mass incarceration in the United States. As they engage in this work, it is important to examine how archivists are responding to the ethical challenges presented by collecting and stewarding records related to incarceration. This article addresses that need by reporting on the findings of qualitative interviews with archivists working at academic repositories with major collections focused on incarceration. This study’s focus on university archives reflects their prominence in undertaking such work, which is likely to continue given these institutions’ comparative autonomy and access to resources. Evaluating this work is urgent because of the vulnerable position of those most impacted by the prison system. Three major themes emerged from the interview data collected in this research: (1) financial and intellectual resources available at universities to support incarceration-related archiving; (2) the university context can provoke ethical anxiety for archivists working with incarceration-related collections; and (3) obtaining meaningful consent is a particularly difficult challenge for archives that steward incarceration materials. Placing these findings within the context of the academy’s carceral entanglements and in dialogue with critical prison studies and critical archival studies scholarship, I argue that ethical incarceration archiving demands a liberatory approach. This approach begins by asking if and how incarceration archiving can help get people free.